2019
DOI: 10.1016/j.celrep.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of FANCD2 Inhibits the FANCD2/FANCI Complex and Suppresses the Fanconi Anemia Pathway in the Absence of DNA Damage

Abstract: Summary Interstrand crosslinks (ICLs) of the DNA helix are a deleterious form of DNA damage. ICLs can be repaired by the Fanconi anemia pathway. At the center of the pathway is the FANCD2/FANCI complex, recruitment of which to DNA is a critical step for repair. After recruitment, monoubiquitination of both FANCD2 and FANCI leads to their retention on chromatin, ensuring subsequent repair. However, regulation of recruitment is poorly understood. Here, we report a cluster of phosphosites on FANCD2 who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 89 publications
(100 reference statements)
0
32
0
Order By: Relevance
“…Surprisingly, we observed that FANCI ub :FANCD2 ub forms filament-like oligomers when bound to dsDNA plasmid ( Figure 6c). Such filaments were not observed in the unmodified FANCI:FANCD2 protein preparation in the absence of presence of plasmid DNA, nor in previous investigations of human or Xenopus FANCI:FANCD2 complexes studied by EM ( Figure 6d-e and (38)(39)(40)).…”
Section: Purification Of Monoubiquitinated Fanci:fancd2 Complex Boundmentioning
confidence: 50%
“…Surprisingly, we observed that FANCI ub :FANCD2 ub forms filament-like oligomers when bound to dsDNA plasmid ( Figure 6c). Such filaments were not observed in the unmodified FANCI:FANCD2 protein preparation in the absence of presence of plasmid DNA, nor in previous investigations of human or Xenopus FANCI:FANCD2 complexes studied by EM ( Figure 6d-e and (38)(39)(40)).…”
Section: Purification Of Monoubiquitinated Fanci:fancd2 Complex Boundmentioning
confidence: 50%
“…However, it's possible that other kinases could further modulate the temporal and/or spatial localization of FANCD2 and FANCI monoubiquitination in vitro or in cells. For example, Casein Kinase 2 phosphorylation of FANCD2 at a cluster of serines between residues 882-898 inhibits its DNA association and subsequent monoubiquitination (Lopez-Martinez et al, 2019), while ATM phosphorylates many residues in FANCD2 independent of monoubiquitination, but only during S-phase and after ionizing radiation (Taniguchi et al, 2002b;Ho et al, 2006). Other kinases with an important role in DNA replication and DNA damage response have yet to be explored, although several such as Chk1 and CDK also phosphorylate subunits in the FA core complex (Deans et al, 2006;Wang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of FANCI also abolishes FANCD2 modification 11 , 12 . Monoubiquitination is a tightly controlled process, and is regulated by phosphorylation 11 , 12 , 25 27 . Altogether this suggests that heterodimerization of FANCD2 with FANCI is essential for this key step in the pathway.…”
Section: Introductionmentioning
confidence: 99%